AN EMPIRICAL MODEL OF PRODUCTIVE ZAKAT UTILIZATION BY ZAKAT INSTITUTIONS TO IMPROVE MUSTAHIQ INCOME - Widiastuti, Tika (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2015)
The research objective was to determine the Zakat Productive Utilization Optimization by charity organizations in Mustahiq Revenue Increases In Surabaya. The research methodology used to be a qualitative approach, with the strategy case study. Data collected by interview mustahiq thirteen recipients of zakat funds productively and two management staff related charity organizations. The analysis technique used is descriptive analysis.The result showed that the Reform zakat productive institutions in this regard PKPU channeled through seven flagship program. One of the programs in order to empower people to improve their economic program is PROSPECTS. This Prospects program, in which there are programs SHG (Self Help Groups) and KUB (Joint Business Group), is a model of productive utilization of zakat by PKPU in increasing revenue mustahiq which according to researchers is optimal. This PROSPEK program, in which there are programs SHG (Self Help Groups) and KUB (Joint Business Group), is a model of productive utilization of zakat by PKPU in increasing revenue mustahiq which according to researchers is optimal. This is evidenced by the increase in revenue mustahiq, smoothness installment payments as well as the ability to sadaqah. Keyword: Mustahiq, Zakat Productive, Utilization